Comparative clinical evaluation of safety and efficacy of commonly used drug-eluting stents in coronary artery disease patients after angioplasty in South India: A retro-prospective multi-center study - Vinoth Prabhu Veeramani, Saranya P. Selvam, Ahmed Mohsen Hamdan (Journal of Applied Pharmaceutical Science, 2019)
Comparative data on safety and efficacy of new generation drug-eluting stents (DESs) are still lacking, the objective of this study is to compare the safety and efficacy of commonly used DESs in patients with coronary artery disease (CAD). Individual data of 146 consecutive patients (119 male and 27 female) stented with different DESs such as Sirolimus (SESs), Everolimus (EESs), or Zotarolimus (ZESs) eluting stents were randomly collected from various hospitals in South India. Pooled data were retro-prospectively analyzed, the primary end-point of this study was determination of major adverse cardiovascular events (MACE) and individual events, which is a composite of cardiac death, target vessel related myocardial infarction (TV-MI), target lesion revascularization (TLR), target vessel revascularization (TVR), stent thrombosis (ST), and in-stent restenosis (ISR) at the end of clinical follow-up which was scheduled at 3 months once up to 1 year after angioplasty. Baseline clinical and cardiac characteristics, angiographic and stent procedural characteristics, efficacy and suspected adverse reactions were compared. Our study results indicate that SESs (a first-generation DES) were found to be non-inferior to EESs and ZESs in reducing risks and remains safe and effective at the end of 1-year clinical follow-up period in CAD patients after angioplasty.
Keywords: Angioplasty, coronary artery disease, drug eluting stents, everolimus, sirolimus, safety and efficacy.